THE LEVEL OF ACTIVITY OF PATHOGENICITY FACTORS OF THE TOKSINFORMING CORYNEBACTERIA CIRCULATORY STAINS - Kalinichenko, S.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The level of activity of pathogenicity factors of circulatory toksinforming Corynebacteria, selected from patients with pathology of ear, nose and throat, healthy carriers and persons inspected with a prophylactic purpose, was studied. It was found out, that all explored stains had a high capacity for adhesion and inactivated complement. The most explored stains had a high indexes of activity of colonization and invasion enzymes. The level of activity of the indicated factors cause, to a great extent, epidemiological consequence of Corynebacteria circulatory stains.